Italiani in catene in Nuova Caledonia. La memoria del bagne in un Paese dell’Oceania insulare - Cristina Bessone (Archivio Antropologico Mediterraneo)
The aim of this article is to provide a preliminary contribution to the presence of Italians in the New Caledonia’s penal colony (the bagne in French) and to analyse their role in the colonial history of this Oceanian Country. After clarifying the importance of the penal colony in the populating process operated by France in the second half of the 19th century, I will illustrate the ways through which some convicts became colonists. I analyse different “types” of Italians convicted in the Caledonian penal structures (prisoners for common crimes, soldiers tried by the Councils of War, political prisoners) and then I focus on some specific convicts-colonists of Italian origin. The concluding part consists in a reflection on the ongoing process of “patrimonialization” of the Caledonian penal colony and on the rediscovery of convict history, concealed for a long time from public view. The bagne memory is an important aspect of the decolonising arena.